An analysis of innovation support programme is an emerging economy: a case study of Malaysia - Dzulkifli Mukhtar; Mohd Hafizie Suhaimi; Muhammad Naqib Mat Yunoh (Intercontinental Management Research Consortium, 2016)
Emerging economies have introduced a number of policies to propel economic development. Policies are acknowledged as powerful tools to promote industrialisation and economic diversification. The feature of these policies are not only confined to established emerging economies but also mid-ranking emerging economies like Malaysia. As the country moves towards a knowledgebased economy, this study provides insight into how a policy comprising a financial initiative introduced by Malaysian Government has been used to enhance capabilities of indigenous small and medium enterprises particularly for innovation. This study is exploratory since it seeks to find out how firms developed and enhanced their innovation capabilities in the presence of government policy. This study found that this policy initiative tends to affect the latter end of the innovation process (i.e. in particular in the exploitation phase) rather to the innovation process in general. This study contributes to closing some of the gaps in research into public support for innovation and development of knowledge-based economy within emerging economies. In particular it identifies the target group and impact of such policy initiative, particularly in the context of policies designed to upgrade firm‟s capacity to carry out new product development process for high-technology products.